Amino Acid Metabolism with Fruit Development in Lycopersicon esculentum Mill under Kumaun Hill Conditions - Mathpal, K.N.; Pant, P.C. (Asian Journal of Chemistry, 2012)
Mature variety of HS-102 and HT-6 of tomato (Lycopersicon esculentum Mill) showed the presence of eleven ninhydrin positive products. Out of these, eight products were indentified as aspartic acid. ornithine, arginine, throneine, α-alanine, methionine, valine and isoleucine through various specific chemical reactions and spectral studies.